2023
DOI: 10.1111/bph.16198
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of tonic endocannabinoid signalling triggers cellular, behavioural and neuroendocrine responses consistent with a stress response

Abstract: Background and PurposeEndocannabinoid (eCB) signalling gates many aspects of the stress response, including the hypothalamic‐pituitary‐adrenal (HPA) axis. The HPA axis is controlled by corticotropin releasing hormone (CRH) producing neurons in the paraventricular nucleus of the hypothalamus (PVN). Disruption of eCB signalling increases drive to the HPA axis, but the mechanisms subserving this process are poorly understood.Experimental ApproachUsing an array of cellular, endocrine and behavioral readouts associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…Endocannabinoids are important tonic regulators of neurotransmitter release in a circuit-wide manner under specific physiological or pathological conditions ( 16 19 , 40 ). Accordingly, bath application of JZL184, an inhibitor of the 2-AG–degrading enzyme monoacylglycerol lipase (MAGL), robustly increased 2-AG levels by ~250% and concomitantly decreased IPSC amplitudes and successful synaptic events in WT mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endocannabinoids are important tonic regulators of neurotransmitter release in a circuit-wide manner under specific physiological or pathological conditions ( 16 19 , 40 ). Accordingly, bath application of JZL184, an inhibitor of the 2-AG–degrading enzyme monoacylglycerol lipase (MAGL), robustly increased 2-AG levels by ~250% and concomitantly decreased IPSC amplitudes and successful synaptic events in WT mice.…”
Section: Resultsmentioning
confidence: 99%
“…While AEA can be synthesized through complex enzymatic pathways in biochemical preparations ( 72 ), NAPE-PLD is known to be the primary enzyme responsible for the synthesis of AEA in vivo ( 37 , 38 ). Accordingly, recent evidence showed that NAPE-PLD is responsible for the AEA tone in the stress response ( 19 , 38 ). However, we found that the synaptic cannabinoid tone is unaffected in NAPE-PLD KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation